If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 60 = 24x Reorder the terms: 60 + 14x = 24x Solving 60 + 14x = 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 60 + 14x + -24x = 24x + -24x Combine like terms: 14x + -24x = -10x 60 + -10x = 24x + -24x Combine like terms: 24x + -24x = 0 60 + -10x = 0 Add '-60' to each side of the equation. 60 + -60 + -10x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -10x = 0 + -60 -10x = 0 + -60 Combine like terms: 0 + -60 = -60 -10x = -60 Divide each side by '-10'. x = 6 Simplifying x = 6
| F(1)=x^58-6x^2+5 | | 6x+4=-2-1 | | x^2-7x+21=0 | | n+(n+3.5)=18 | | 25+4(3n-12)=1 | | x+6.1=11.1 | | 2(z-1)+3= | | -0.008x^2+1.2x+200=0 | | 14=7x+7 | | 5y+5x=25 | | 3x+9=x-9 | | 12+4x+90=180 | | y(f)=27x^2-27x-12 | | 6x+1+2x=3x+46 | | 79+(8x-11)=180 | | -4y-2+7y=20 | | A=10x | | -16t^2+100t=50 | | 12z-4=10z | | a/2-18=-7 | | Gr=a | | 4z-3=10z-18 | | .15z+2=6.5 | | X+24+4x=-7-4x-14 | | .15z-2=6.5 | | 7k=64 | | 2(3c-1)-2=2c+8 | | u^2=49 | | 7*4-n=-14 | | 5x-5=115 | | 10x^2-53x+15=0 | | 12+9n=8-4n |